panda's guide to mental wellbeing - Edwards, Lisa; Edwards, Lisa; Lawston, Rachel; Peutrill, Sarah; Roberts, Sian (London Franklin Watts, 2022)
Spend a day in the forest with Sloth and find out how she keeps so calm! This book has lots of advice for how to manage emotions and stay calm for its human readers. Topics include doing one thing at a time, getting enough rest, exercise and asking others for help
Science
Keywords: science